Clays and Clay Minerals, Vol. 60, No. 2, 176–185, 2012. - Dohrmann, Reiner; Genske, Dieter; Karnland, Ola; Kaufhold, Stephan; Kiviranta, Leena; Olsson, Siv; Plotze, Michael; Sanden, Torbjorn; Sellin, Patrik; Svensson, Daniel; Valter, Martin (The Clay Minerals Society, 2012)
Bentonites are candidate materials for encapsulation of radioactive waste. The cation exchange capacity (CEC) has proven to be one of the most sensitive parameters for detecting changes in mineral properties in bentonite-alteration experiments. An interlaboratory study of CECs and exchangeable cations for three reference bentonite buffer materials that were used in the Alternative Buffer Material test (ABM) project in A¨ spo¨, Sweden, was conducted to create a suitable database. The present study focused on CEC accuracy and compared CEC methods where care was taken to prevent dissolution of soluble minerals such as calcite and gypsum. The overall quality of the CEC and exchangeable cation values measured using non- Cu-trien CEC methods were good, with CECs of 74-91-0.5-3.3 meq/100 g and exchangeable cation values of 22-61-1.2-3.9 meq/100 g Na+, 7-23-0.8-1.5 meq/100 g Mg2+, and 19-39-0.8-1.6 meq/ 100 g Ca2+. The precision was comparable to the standard Cu-trien method even for exchangeable Ca2+, although the laboratories used different solution/solid ratios and reaction-time parameters for Cu-trien which affect carbonate dissolution. The MX80 and Dep.CAN bentonite exchangeable Ca2+ values were more accurate than standard-Cu-trien values. Using the optimized methods of this study, MX80 and Dep.CAN exchangeable Ca2+ values averaged 20.2-1.6 and 38.8-1.4 meq/100 g which amounts to ~70% of the inflated Cu-trien values. A more complex analysis of the CEC data using different methods, anion analyses, and mineralogical analysis is necessary to obtain plausible and accurate CEC values. Even with a more complicated analytical procedure, the CEC and exchangeable cation values were still not accurate enough because of excess anions. Chloride, sulfate, and dolomite might have increased the exchangeable Na+, Mg2+, and Ca2+ values.
Interlaboratory Cec And Exchangeable Cation Study Of Bentonite Buffer Materials: Ii. Alternative Methods
gsccm60207-doh2.pdf -- 199KB
Keywords: Periodicals; Geology; Ammonium Acetate; Ammonium Chloride; Bentonite Buffer; CEC; Cu-trien5xcalcite; Exchangeable Cations; Interlaboratory Study